Silicon, an important exposure marker in vivo in silicosis research - Wang, Hongli; Cui, Jie; Hao, Xiaohui; Guo, Lingli; Zhao, Jinyuan; Wang, Ruimin; Liu, Heliang (International archives of occupational and environmental health, 2021)
Purpose The degree of silicosis exposure is closely related to the progress of silicosis. At present, we use animal and human studies to explore whether silicon can be an important exposure marker in the development of silicosis. Methods Rats were randomly divided into 2 groups: (1) controls; and (2) silicosis. Rats in the silicosis group were killed at 4, 8, 12, 16, 24 h, 3, 7, 14, 21, and 28 days. Hematoxylin–eosin (HE) and immunohistochemistry (IHC) were performed to observe the histomorphology of lung tissue. The expression levels of CC16 and SP-D were detected using ELISA kits. In addition, we conducted a population study. Workers who have been selected to work in an iron mine for more than 1 year as research objects. The population was divided into four groups: silicosis exposure group (workers exposed to silica dust for more than 1 year in an iron mine were selected); patients group (silicosis patients); observation group (evidence of disease not meeting formal diagnostic criteria) and control group. Both the levels of trace silicon in the urine and blood of rats and human subjects were measured with ICP-MS. Results Serum levels of silicon were immediately increased in rats exposed to silicon dust. Similarly, our population study revealed that the silicon level in the silica exposure group and the observing group (exposed but no obvious symptoms) were significantly increased over that of the control group ( P < 0.05). In subjects with extended exposure to silica, the serum and urine silicon level in exposed workers appeared to rapidly increase, reaching its peak in 1–5 years, followed by a gradual decline thereafter. Workers exposed to dust for less than 10 years were divided into subgroups by 2-year limit. The levels of serum silicon, urine silicon, TGF-β1, and TNF-α were significantly higher than that of control group. Conclusion Changes of the serum levels of silicon occurred earlier than the expression of cytokines such as TNF-α, TGF-β 1 , CC16, and SP-D. The level of silicon in workers rapidly increased after exposure to silica, and the change occurred before the expression of TGF-β1 and TNF-α. As a whole, the findings suggest that determining the level of silicon in vivo might be an effective exposure marker in the diagnosis and pathogenesis of silicosis.